2017
DOI: 10.1177/1350650117705568
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the angular distribution of a grooved surface texturing on the generation of friction-induced vibration and noise

Abstract: This study experimentally investigated the influence of angular distribution of a grooved surface on wear properties as well as friction-induced vibration and noise characteristics. The surfaces of brake disc material were modified by cutting grooved surfaces with different angular distributions. The differences between the grooved and smooth surfaces in friction and wear and friction-induced vibration and noise were evaluated. This was performed via a pad-on-disc test configuration where the brake pad materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The RPTS also shows severe wear situation with significant furrow and material transfer on the surface. In addition, as the round pits are filled with wear debris, the sizes of some round pits are seriously reduced and part of round pits are even disappeared, which accordingly triggers the generation of FIV phenomenon [23,24].
Figure 7 The worn surface characteristics of smooth surface (a), RPTS (b), SPTS (c) and GTS (d) observed by SEM.
…”
Section: Resultsmentioning
confidence: 99%
“…The RPTS also shows severe wear situation with significant furrow and material transfer on the surface. In addition, as the round pits are filled with wear debris, the sizes of some round pits are seriously reduced and part of round pits are even disappeared, which accordingly triggers the generation of FIV phenomenon [23,24].
Figure 7 The worn surface characteristics of smooth surface (a), RPTS (b), SPTS (c) and GTS (d) observed by SEM.
…”
Section: Resultsmentioning
confidence: 99%
“…25-35% reduction in the friction coefficient, 15-40% vibration reduction, at relatively high loads (p H ¼ 0.7-1.0 GPa) at rolling/sliding velocities (0.04-0.16 m/s). [3][4][5][6] Significant reduction in the frictional torque, vibration amplitude, and temperature rise are also reported with grease-lubricated textured thrust ball bearing. 10 Looking at the encouraging results with concentrated textured contacts, it is worth exploring here for enhancing the tribological behaviors of reciprocating lubricated point contacts at high loads (up to 3 GPa) using low and high viscous oils.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, surface texture has emerged as a viable technology for improving the tribodynamics behavior of concentrated contacts. [3][4][5][6][7][8][9][10] It is found that certain textures reduce the vibration and friction coefficient at the lubricated contacts due to the enhanced value of damping due to better lubrication. Lubricated textured point contacts have yielded beneficial results i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have begun to use various surface treatment methods to study the in uence of surface treatment of brake discs/plates on brake friction vibration and noise. Zhang Kangzhi et al [7] used the nite element analysis method to explore the in uence of friction plate surface grooving on the friction vibration characteristics of the system, and the results showed that the grooving of the disk surface had a certain degree of suppression effect on the friction vibration noise of the system. Liu et al [8] cut different angle grooves on the surface of the brake disc, and the in uence of grooves distributed at different angles on the friction vibration and noise of the brake disc was studied by experimental method, and the results showed that the ability of the brake disc to suppress noise was closely related to the angle distribution of the surface groove.…”
Section: Introductionmentioning
confidence: 99%